(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article deals with the linguistic expression of the emotional behavior of literary heroes. It is emphasized that lexeme on the notation of nonverbal behavior of characters in artistic texts are the means of depicting their psychological condition and the stylization of direct live communication. It is substantiated that the reproduction of such extra-linguistic means as tone and volume of voice, breath, laughter, etc. help the author to reveal the inner world of the characters, and thus deepen the psychology of the work.